Hesquiat Root Digger - Curtis, Edward S., 1868-1952 (1915)
In 1906, Edward S. Curtis received funding from J.P. Morgan to begin work on "The North American Indian," a twenty volume set of photographs and text documenting Native American tribes throughout the western United States. The eleventh volume, featuring the Nootka, Clayoquot and Haida tribes, was published in 1916. "Nootka women very commonly wore bark cape folded over the head, to protect the forehead from the tump-line, when carrying the burden-basket. The proper use of the cape was to shed rain." Harriet Bullitt Master images photographed at 300 ppi, 48 bit color, and saved as TIFF files. Adobe Photoshop used to crop, resize and convert to JPEG format. Master image file size: 306,760,104 bytes. Published No Copyright - United States This item was published prior to 1923 and is in the public domain. No known copyright restrictions identified by the library at the time of scanning in March 2018.